Multilayered specification of the T-cell lineage fate - Rothenberg, Ellen V. (2010)
T-cell development from stem cells has provided a highly accessible and detailed view of the regulatory processes that can go into the choice of a cell fate in a postembryonic, stem cell-based system. But, it has been a view from the outside. The problems in understanding the regulatory basis for this lineage choice begin with the fact that too many transcription factors are needed to provide crucial input: without any one of them, T-cell development fails. Furthermore, almost all the factors known to provide crucial functions during the climax of T-lineage commitment itself are also vital for earlier functions that establish the pool of multilineage precursors that would normally feed into the T-cell specification process. When the regulatory genes that encode them are mutated, the confounding effects on earlier stages make it difficult to dissect T-cell specification genetically. Yet both the positive and the negative regulatory events involved in the choice of a T-cell fate are actually a mosaic of distinct functions. New evidence has emerged recently that finally provides a way to separate the major components that fit together to drive this process. Here, we review insights into T-cell specification and commitment that emerge from a combination of molecular, cellular, and systems biology approaches. The results reveal the regulatory structure underlying this lineage decision.